Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/pam.21784
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Subnational Fiscal Policies on Economic Growth: A Dynamic Analysis Approach

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Investors would be discouraged by high interest rates and accumulate less capital which would upshot into low economic growth. Some authors have found a direct link between investment and economic growth (Romp & De Haan, 2005;Shrithongrung & Kriz, 2014). Baseerit (2005) posited that the earlier stage of borrowing is normally marked with enhanced growth resulting from modest debt level.…”
Section: Unit Root Test and Ardl Resultsmentioning
confidence: 99%
“…Investors would be discouraged by high interest rates and accumulate less capital which would upshot into low economic growth. Some authors have found a direct link between investment and economic growth (Romp & De Haan, 2005;Shrithongrung & Kriz, 2014). Baseerit (2005) posited that the earlier stage of borrowing is normally marked with enhanced growth resulting from modest debt level.…”
Section: Unit Root Test and Ardl Resultsmentioning
confidence: 99%
“…There is lot of financial analysis left to do here (see Clair 2012;Hendrick and Crawford 2014;Marlowe 2012;Srithongrung and Kriz 2014). We have merely scratched the surface.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Sánchez-Juárez and García [31] found with data of the Mexican economy for the period 2003-2011 that the relationship between production and public investment made by sub-national governments of the northern border is negative, which they attributed to the effect of displacement of private investment or that had a short temporary sample (on this last point, see the work of Castillo and Garcia [32]). Shrithongrung and Kriz [33] show with sub-national data of the American economy and the method of Panel Vector Autoregression, that public capital has a positive effect on growth in the short and the medium term. On the other hand, Shrithongrung and Sánchez-Juárez [9], with data of sub-national governments of Mexico, confirm that public investment has positive effects on the production in both the short and the long term.…”
Section: (3)mentioning
confidence: 99%